(untitled) (Indian Journal of Public Health Research & Development, 2021)
Introduction: About 50% of infertility is attributed to male factor. Semen analysis is the cornerstone of the diagnosis, and treatment of male infertility. The quality of semen varies from country to country. The present study was undertaken to evaluate semen abnormality of infertile Iraqi men as compared to other countries and to determine whether these parameters are correlated to each other. Patients and Method: The seminal fluid profile was classified according to the WHO manual (2010). Briefly, asthenozoospermia (i.e. progressive motility of spermatozoa below 32%), oligozoospermia (i.e. spermatozoa concentration below 15x106 per ml), teratozoospermia (i.e. morphologically normal spermatozoa below 4%), asthenoteratozoospermia, oligoasthenozoospermia, oligoasthenoteratozoospermia, oligoteratozoospermia, and azoospermia (absence of spermatozoa in the ejaculate) Results: The most striking abnormality is the high percentage of patients withabnormally low morphology score (72.09%). The majority of cases have isolated abnormality (teratozoospermia; 48.84%). Asthenoteratozoospermia (ATZ) was found in 10.47% and oligoasthenozoospermia (OAZ) and oligoteratozoospermia (OTZ) in 8.14% of cases. The least common pattern was necroteratozoospermia (NTZ) and oligonecroteratozoospermia (ONTZ) 1% each. Azoospermia was encountered in 3.49% of cases. Conclusion: Abnormalsperm morphology is the best indicator of infertility and teratozoosperma is the most common finding in abnormal spermiogram.